BUSINESS STUDENTS CAREER INTEREST IN ACCOUNTING PROFESSION: AN EXPLORATORY STUDY IN TURKEY - Yardimcioglu, Mahmut; Ada, Sebnem (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Accounting is a very important profession in todays contemporary business environment. On the other hand, it is also becoming more difficult to find qualified graduates specialized in accounting. Therefore, in order to foster students to be interested in accounting, it is of utmost importance to identify the factors that determine students interest in this field. This study identifies and investigates the factors (i.e., career outcome expectation, career challenge, social influence, and academic performance in accounting) that are likely to influence students career interests in the field of accounting. A structured survey was administered to university students located in a province in Turkey. The findings of this research study reveal that students that aim to pursue a challenging career; that are influenced by other people related to their career decisions; and that have greater academic performance in accounting will be interested in pursuing a career in the field of accounting.